Drug Delivery: On‐Chip Self‐Assembly of a Smart Hybrid Nanocomposite for Antitumoral Applications (Adv. Funct. Mater. 10/2015). (March 2015) - Herranz‐Blanco, Bárbara; Liu, Dongfei; Mäkilä, Ermei; Shahbazi, Mohammad‐Ali; Ginestar, Eloy; Zhang, Hongbo; Aseyev, Vladimir; Balasubramanian, Vimalkumar; Salonen, Jarno; Hirvonen, Jouni; Santos, Hélder A.
Abstract : On page 1488, B. Herranz‐Blanco, H. A. Santos, and co‐workers fabricate a multistage drug delivery nanocomposite, comprising porous silicon nanoparticles and micellar pH‐responsive polymers, by microfluidic nanoprecipitation. The drug‐loaded multistage platform shows high cytocompatibility, pH‐dependent cell growth inhibition capacity, and reduced internalization by phagocytic macrophage cells. This nanocomposite is a good candidate for further development as a platform for cancer drug delivery.